INVESTIGATION ON PHARMACOGNOSY AS WELL AS THE ANTIOXIDANT, ANTI-INFLAMMATORY POTENTIAL OF THE KATHA POWDER - SHARMA, PANKAJ; L, RAJU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to investigate the pharmacognosy as well as the antioxidant, anti-inflammatory potential of the Katha powder. Methods: The Coarsely dried chips of Acacia catechu heartwood were treated with 10 % hydro-alcoholic solution to obtain Katha as the final product. The powdered Katha was standardized through pharmacognostic parameters. This Katha power is showing the good solubility in the hot water having astringent in the taste. The powder microscopy of the Katha powder is to be demonstrated fragments of acicular crystals, fibers, and bordered pitted vessels. Katha powder antioxidant potential is to be accessed by using the 2, 2-diphenyl-1-picryl hydrazyl assay and NO Scavenging assay using ascorbic acid as a standard drug. Further, the Katha powder is to be subjected for the assessment of its anti-inflammatory potential by the use of heat-induced hemolysis as well as hypotonicity-induced hemolysis approach by the use of the aspirin or diclofenac sodium as a standard drug. Results: Microscopical investigations were showed that Katha showing the presence of fragments of acicular crystals, fibers, and bordered pitted vessels. In vitro study shows that the Katha powder has excellent antioxidant as well as anti-inflammatory potential in a dose-dependent manner in comparison of the result of heartwood of A. catechu. Conclusion: So from this investigation, it is to be suggested that the Katha powder is rich in the phenolic compound and the experimentation study shows that the drug is to possess a good antioxidant as well as anti-inflammatory property.